Data needs to be a priority - Halford, Alexa J.; Chen, Thomas Y.; Rastaetter, Lutz (Frontiers in Physics, 2022)
Findable, Accessible, Interoperable, and Reusable (FAIR) data are essential to heliophysics, indeed all scientific research. The principals of FAIR data ensure the reusability and finability of data as well as its long term care. The goal is that the data are accessible for the ongoing process of discovery and verification and can be used on its own or with newly generated data in future studies leading to new innovations. With the onset in the previous decades of NASA and other agencies requiring mission data to be open to the public, great strides have been made towards FAIR data. Continued improvements with our metadata, data archives, data portals, and the addition of DOIs to cite data will ensure data will be FAIR, enabling further scientific discoveries, reproduciblility of results, longitudinal studies, and verification and validation of models. Currently, not all the data collected is findable and open, and not all data on archives have DOIs. Within this paper we make recommendations to prioritize resources needed to satisfy FAIR data principles, treating them as a fundamental research infrastructure, rather than a simple research product. • Data collection, preparation, archiving, and accessibility needs to be a priority • Data collection, preparation, archiving, and accessibility needs dedicated, sustained funding support. • Data needs to be accessible through investment in infrastructure, tools to access and read the data and personnel to maintain this data and IT infrastructure. • Data needs to be collected in sustained ways to enable further science, and specifically, model validation efforts